Part of the expression in a book reads:

$\displaystyle x+(x + 1) = 25$

which becomes

$\displaystyle 2x + 1 = 25$

My question is how does the above expression become $\displaystyle 2x+1=25$?

I thought when you see an expression such as $\displaystyle x+(x+1)$ there is a hidden integer, a 1 therefore it should read $\displaystyle x+1(x+1)=25$. If that is the case shouldn't it be $\displaystyle 2x + 2 = 25$?

Obviously I am not understanding it correctly, I just wanted to show my incorrect logic.

Thanks